2019
DOI: 10.1111/jedm.12207
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Person‐Fit Statistics Under Model Misspecification

Abstract: In educational and psychological measurement, a person‐fit statistic (PFS) is designed to identify aberrant response patterns. For parametric PFSs, valid inference depends on several assumptions, one of which is that the item response theory (IRT) model is correctly specified. Previous studies have used empirical data sets to explore the effects of model misspecification on PFSs. We further this line of research by using a simulation study, which allows us to explore issues that may be of interest to practitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…It is also more powerful for the longer test lengths, but caution in interpretation is warranted because of a few inflated Type I error rates under the null for each statistic. As for M 2 , it has low-to-moderate power, which is consistent with prior research (Hong et al, in press). Similarly, prior research has found S X 2 to have low-to-moderate power in detecting this form of misspecification, which is consistent with the results in Table 4.…”
Section: Simulation Studysupporting
confidence: 89%
“…It is also more powerful for the longer test lengths, but caution in interpretation is warranted because of a few inflated Type I error rates under the null for each statistic. As for M 2 , it has low-to-moderate power, which is consistent with prior research (Hong et al, in press). Similarly, prior research has found S X 2 to have low-to-moderate power in detecting this form of misspecification, which is consistent with the results in Table 4.…”
Section: Simulation Studysupporting
confidence: 89%
“…Other combinations of statistics could also be explored. Third, it would be useful to examine the impact of model misspecification on the performance of the new statistics (Hong et al, 2020; Meijer & Tendeiro, 2012). Fourth, the statistics could be extended to multidimensional tests (Albers et al, 2016; Drasgow et al, 1991; Hong et al, 2021) and/or tests with polytomous items (Hong et al, 2021; Sinharay, 2016a).…”
Section: Discussionmentioning
confidence: 99%